MECHANISM FOR MANAGING THE DEVELOPMENT OF RURAL AREAS BASED ON STATE SUPPORT FOR SMALL AND MEDIUM-SIZED BUSINESSES - POPADYNETS, Nazariy; DANYLO, Svitlana; KOTSKO, Taras (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the theoretical and methodological justification of the mechanism for managing the development of rural areas based on state support for small and medium-sized businesses in the context of decentralization, military challenges, and post-war reconstruction in Ukraine. It is argued that the traditional model of rural development, focused primarily on supporting large-scale agricultural production, is insufficient to ensure the reproduction of human capital, diversification of the economy, and improvement of the quality of life of the rural population. The expediency of transitioning to an integrated, territorially oriented management model, within which small and medium-sized businesses are considered a system-forming factor of the socio-economic stability of rural communities, has been proven. The article proposes the author’s interpretation of the mechanism for managing the development of rural areas as a multidimensional system of goals, principles, instruments, and coordination actors, focused on reconciling the interests of the state, business, and local communities. The key subsystems of the mechanism are identified and described in detail: diagnostic and analytical, economic and financial, organizational and managerial, social and infrastructural, spatial, and security and environmental. The need to form integrated systems for monitoring community development, applying a project-based approach to supporting entrepreneurship, developing the institutional infrastructure of financial intermediation, and introducing spatially differentiated instruments of state support for small and medium-sized businesses is substantiated. It is emphasized that in conditions of martial law and post-war recovery, the effectiveness of the rural development management mechanism is determined by the ability to adapt support instruments to increased security, environmental, and socio-economic risks, as well as to ensure partnership between public authorities, the business community, and communities.